NEUROFEEDBACK DAN REGULASI EMOSI SEBAGAI INTERVENSI PENDUKUNG BAGI ANAK SPEECH DELAY DENGAN KOMORBID ADHD: SCOPING REVIEW - Firmawati; Sari, Desi Purnama (JIP (Jurnal Intervensi Psikologi), 2026)
ABSTRACT: Approximately 25–40% of children with speech delay present with comorbid ADHD, a condition that exacerbates impairments in language development, attentional control, and emotion regulation. However, a systematic synthesis integrating neurofeedback (NFB) and emotion regulation interventions for this specific population remains absent. This scoping review aimed to map the available empirical evidence on NFB and emotion regulation interventions for children with concurrent speech delay and ADHD, while proposing an original integrative conceptual model. Following the Arksey and O’Malley framework and PRISMA-ScR guidelines, a systematic search was conducted across PubMed, Scopus, and Web of Science (2010–2024). Twenty studies met the inclusion criteria. The findings confirmed a critical evidence gap, as no existing literature directly targeted this comorbid population. Nevertheless, NFB interventions—particularly theta/beta and coherence-based protocols—demonstrated significant improvements in attentional and language functions. Recent meta-analyses underscore that protocol standardization and an adequate cumulative dose (>1,260 minutes) are prerequisites for reliable efficacy. Conclusively, this review introduces the MERLIN Model (Mind-Emotion Regulation and Language Integrative Neurofeedback) as a novel conceptual framework bridging neurobiological, behavioral, and affective dimensions. Rigorous Randomized Controlled Trials (RCTs) specifically targeting this comorbid population are urgently needed.  Key words: ADHD, emotional regulation, neurofeedback,  scoping review, speech delay. ABSTRAK: Sekitar 25–40% anak dengan speech delay menyandang ADHD, komorbiditas yang memperberat hambatan perkembangan bahasa, atensi, dan emosi. Namun, belum ada sintesis sistematis mengenai integrasi neurofeedback (NFB) dan regulasi emosi untuk populasi ini. Penelitian scoping review ini bertujuan untuk memetakan bukti empiris mengenai intervensi NFB dan regulasi emosi pada anak dengan speech delay disertai komorbiditas ADHD, sekaligus mengusulkan sebuah model konseptual integratif baru. Mengacu pada kerangka kerja Arksey dan O’Malley serta pedoman PRISMA-ScR, pencarian literatur dilakukan pada basis data PubMed, Scopus, dan Web of Science (2010–2024). Dua puluh studi memenuhi kriteria inklusi. Hasil menunjukkan kesenjangan bukti kritis: Belum ada studi yang menyasar populasi komorbid tersebut. Meskipun demikian, NFB, terutama protokol theta/beta dan berbasis koherensi, signifikan memperbaiki fungsi atensi dan bahasa. Metaanalisis terkini menegaskan standardisasi protokol dan dosis adekuat (>1.260 menit) sebagai prasyarat efikasi. Penelitian ini mengusulkan MERLIN Model (Mind-Emotion Regulation and Language Integrative Neurofeedback) sebagai kerangka konseptual baru yang menjembatani dimensi neurobiologis, perilaku, dan afektif. Randomized Controlled Trial (RCT) ketat pada populasi komorbid ini sangat dibutuhkan.  Kata kunci: ADHD, neurofeedback, regulasi emosi, scoping review, speech delay.